Performance optimization of absorption refrigeration systems using Taguchi, ANOVA and Grey Relational Analysis methods - Canbolat, A. S.; Bademlioğlu, Ali Hüsnü; Arslanoglu, N.; Kaynakli, O. (Elsevier Sci Ltd, 2019)
There are various factors having an impact on the energetic and exergetic performance (i.e., COP and eCOP) of an absorption refrigeration systems (ARS) such as the temperatures of the generator, condenser, evaporator and absorber, effectiveness of solution, refrigerant and solution-refrigerant heat exchangers and isentropic efficiency of the solution pump. Many studies have focused on these process parameters, but the importance order and contribution ratios of the parameters due to thermodynamic performance have not been determined by using statistical methods. Firstly, in this study, cycles' thermodynamic model is established and the variation of the COP and eCOP are calculated for different working conditions with different parameters ranges. The effects of these parameters on the COP and eCOP are examined separately on a statistical basis. The importance order of the parameters are determined by using Taguchi and ANOVA methods and the results are compared. Optimum operating conditions are determined by means of statistical analysis for the COP and eCOP. Under these operating conditions, the COP and eCOP of the system are calculated as 0.697 and 0.2829, respectively. Furthermore, for the simultaneous maximization of these two performance indicators, Taguchi-Grey Relational Analysis (GRA) is used. By using this analysis, importance order of the examined parameters on multiple performance characteristics are determined. The absorber and evaporator temperatures are the most efficient parameters on multiple performance characteristics with a contribution ratio of 29.66% and 26.34% of the total effect while the least efficient parameters are the pump efficiency and effectiveness of solution refrigerant heat exchanger with a contribution ratio of 0.48% and 2.41%, respectively. For the best condition considering the multiple performance characteristics, COP and eCOP of the system are found as 0.6255 and 0.2829, respectively. (C) 2019 Elsevier Ltd. All rights reserved.
, Nurullah/0000-0003-4970-4490
Keywords: Absorption refrigeration system; Taguchi method; Grey relational analysis; ANOVA; COP; eCOP